Purpura fulminans, TEN, and disseminated herpes simplex: An unexpected combination - Sebastian Holm; Viktoria Thurfjell; Paola Lara‐Valencia; Fredrik Huss (Clinical Case Reports, 2022)
Abstract Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and purpura fulminans (PF) are all rare conditions. A combination of these 3 conditions together with a viral infection is very rare. A 52‐year‐old, previously healthy woman which developed SJS, potentially due to a reaction to CT contrast, although this is still unknown. This developed into TEN on day 10 of the initial admission, the patient scored 3 points on SCORTEN. On day 12 from initial admission, she developed unexpected multiorgan failure and PF. The patient passed away 2 days later, the autopsy demonstrates herpes simplex virus in the bladder and lungs on immunohistological staining. Our clinical case encountered the challenge of differentiating TEN and PF. The microscopic and immunochemical examination confirmed the clinical suspicion of PF but also a disseminated herpes simplex infection. We speculate the clinical route of this case started SJS and TEN, leading to superimposed infection with three different types of bacteria, confirmed in blood cultures, and a disseminated viral infection. The combination of all these diagnoses are very rare, no similar case has been described in adults to the authors’ knowledge. We recommend a prompt diagnosis and early recognition of both bacterial and viral infections to prevent the development of PF.